2016
DOI: 10.1007/s11999-016-4984-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Pediatric Orthopaedics: What Are the Implications for the Future Workforce?

Abstract: Background Although the number of women in surgical specialties has increased dramatically over the past two decades, little research exists regarding how a surgeon's gender impacts job selection and practice models. Because the number of women specializing in pediatric orthopaedics continues to increase, it is important to understand how one's gender affects practice choices and how this may affect the future workforce. Conclusions Although the numbers are small given the specialized nature of pediatric ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 13 publications
1
29
0
2
Order By: Relevance
“…However, women assigned greater importance to call schedule than men, and a higher proportion of women, although not statistically significant, reported wanting to practice part-time than men. Studies in other medical specialties report that more females practice part-time than males [1,2]. This difference can have a significant implication to a field as the workforce may have to train additional physicians to accommodate those who will not work full-time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, women assigned greater importance to call schedule than men, and a higher proportion of women, although not statistically significant, reported wanting to practice part-time than men. Studies in other medical specialties report that more females practice part-time than males [1,2]. This difference can have a significant implication to a field as the workforce may have to train additional physicians to accommodate those who will not work full-time.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in pediatric orthopedic surgery was that women tended to seek more academic positions than men [2]. In addition, the AUA 2017 census reported that fewer women were in PP than men [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps patients perpetrate disparities, with decisions of surgeon choice rooted in social norms associating orthopaedic surgery with the male gender. For example, does the gender difference in surgical caseload reflect such patterns [1]? Regrettably, my takeaway after reviewing studies on discrepancies among academic physicians [7,8] is that systemic discrimination is real.…”
Section: Pervasive Systemic Discriminationmentioning
confidence: 99%
“…Amoli 2 la ubica a esta como una actividad profesional denominada "workforce" por la cirugía musculoesquelética diferenciándola de partes blandas como la Cirugía Plástica.…”
unclassified